Improving Madrasah Quality Through Leadership and Capacity Building - Rizqi Nur Faizin; Ainur Rofiq; Ali Wafa; Ravilla Naflah Salsabila (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2024)
This research aims to understand in depth the process of improving the quality of madrasahs through implementing a leadership system to strengthen human resource capacity at one of the Tsanawiyah Madrasahs in Banyuwangi Regency. In exploring the meaning behind school quality assurance practices, researchers used a qualitative approach in the form of case studies. Various data collection methods, such as interviews, observation, and documentation, were used to ensure the accuracy and validity of information related to this research theme. Research data was collected, reduced, presented, and conclusions drawn. The results of this research highlight that efforts to improve the quality of madrasahs through implementing a leadership system to strengthen human resource capacity at Tsanawiyah Madrasahs in Banyuwangi Regency consist of several strategic steps, including policy analysis, organizational commitment, management support, workforce development, and increasing innovation. These findings emphasize the importance of effective leadership management and capacity building to improve individual competence and quality of performance and strengthen their commitment and loyalty to the madrasah.